SISTEM PAKAR MENDETEKSI KERUSAKAN PADA GITAR AKUSTIK MENGGUNAKAN METODE BACKWARD CHAINING BERBASIS WEB - Tanjung, Rivaldy Ramadhan; Hutabri, Ellbert (LPPM Universitas Putera Batam, 2025)
In artificial intelligence world, expert systems are a form of AI (Artificial Intelligence) designed to solve problems aiming the thinking process of an expert. Website-based expert system can detect various acoustic guitars damage. This expert system uses the backward chaining method, where the process starts from the damage, then asks several questions related to the symptoms of damage that occur on the acoustic guitar, then matches them. answers with existing hypotheses, such as a problem with the sound or some component that is not working. With the existing information, the system will perform an analysis and provide diagnosis results and repair recommendations according to the damage to the acoustic guitar. One of the advantages of this expert system is that it is website-based, because it is accessible anytime. It allows beginners, professionals and technicians to detect and repair damage to their acoustic guitar.